HISTOMORPHOMETRIC FEATURES DAN PERCENTAGE OF NEUTROPHILS AND BASOPHILS IN BALI CATTLE BASED ON CONVENTIONAL SYSTEM - Angela Ivanka Benedicta; Ni Ketut Suwiti; Ni Nyoman Werdi Susari; Ni Luh Eka Setiasih; I Ketut Suatha; Anak Agung Sagung Kendran (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The Bali cattle rearing system in Bali is generally carried out using a conventional system. Conventional rearing is characterized by raising livestock on an area of land with food sources originating from the environment, so that the health of Bali cattle receives less attention. This maintenance method affects the body's resistance, one of the indicators is white blood cells. This study aims to determine the histology, morphometry and white blood cell count of neutrophils and basophils in Bali cattle based on conventional system. This research used samples in the form of blood from 30 Bali cattles, located in Bulian Village, Kubutambahan District, Buleleng Regency. Blood smears were fixed and stained using MDT IndoReagen®. Morphometric measurements of neutrophil and basophil white blood cells using the EP View application with 1000x magnification. Counting the number of neutrophils and basophils is done by counting from the edge of the field to the next edge, up to 100 leukocyte cells. The results showed that neutrophils have light pink, thin granular cytoplasm and have a segmented nucleus of 3-6 dark purple lobes with an average diameter of 5.79±0.57 µm. Basophils have purple granular cytoplasm and have a dark purple nucleus that is multi-segmented (polymorphonuclear) with an average diameter of 6.53±0.78 µm. The histological structure of neutrophils and basophils in Bali cattle based on conventional system is similar to neutrophils in other ruminants. The total number of neutrophil white blood cells was 14% and basophils was 8%. Further research needs to be done regarding health status by looking at other indicators such as the presence of white blood cells, eosinophils, lymphocytes and monocytes in Bali cattle based on conventional systems.